SHARIAH DECONSTRUCTION: THE THOUGHTS OF ABDULLAHI AHMED AN-NA'IM - Yurike Siti Mariyam; Mohamad Yufidz Anwar Ibrohim; Achmad Fageh; Anni 'Ilma Rosyidah; Habib Hidayatullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Abdullahi Ahmed an-Na'im's Sharia Deconstruction is an alternative thought in sharia-based law reform. This thinking tries to reflect back on the dominant authority and interpretation in the Islamic legal tradition, by proposing an approach that is based on universal values such as fairness, fairness, and protection of human rights. An-Na'im argues that Islamic law must be seen as a social construction formed through a historical process and a particular context, and must be reconstructed in accordance with the demands of modern times. An-Na'im's sharia deconstruction approach also emphasizes the importance of freedom of religion and equality in society. He proposed peace between religion and the state, in which the state must treat neutrally and treat all citizens without taking sides or discriminating against certain religions. This thinking aims to create a legal system that is more inclusive and democratic, which involves the active participation of the community in determining appropriate laws and policies. Even though an-Na'im's deconstruction of sharia provides an alternative perspective in sharia-based legal reform, this view is still the subject of presumption among Islamic scholars and scholars. There are various viewpoints in interpreting and applying Islamic law, and the an-Na'im approach is only one of many existing approaches.